Price dispersion and inflation: New facts and theoretical implications - Viacheslav Sheremirov (Federal Reserve Bank of Boston, 2015)
In macroeconomic models, the level of price dispersion - which is typically approximated through its relationship with inflation - is a central determinant of welfare, the cost of business cycles, the optimal rate of inflation, and the tradeoff between inflation and output stability. While the comovement of price dispersion and inflation implied by standard models is positive, I find that in the data, it is negative. This is due to transitory price changes (sales): if sales are removed from the data, the comovement of price dispersion and inflation turns positive. Nevertheless, I show that a wide variety of price-stickiness models that ignore sales cannot quantitatively match the comovement even for regular prices. Modeling sales explicitly helps to reconcile theory with the data: a Calvo model with sales quantitatively matches both the negative comovement for posted prices and the positive comovement for regular prices. Thus, sales play a pivotal role in explaining the properties of regular prices; models without sales - failing to reproduce fundamental properties of price dispersion - may significantly mismeasure welfare and its determinants.
Keywords: E17; E31; E37; E40; E52; 330; inflation; price dispersion; sales; sticky prices